Musicalização para bebês em um projeto de extensão universitária : o lugar da família nas práticas musicais das crianças - (:unkn) unknown (Universidade Federal do Pampa, 2022)
This research was based in an extension program called “Musicalização para bebês e crianças” from Universidade Federal do Pampa’s Music course. Being a monitor and a researcher in this project made me reflect on aspects of daily musical practices from the families’ point of view, based on the Music Learning Theory by Gordon (2000). The main objective was to understand how the families’ musical memories reflect on the babies’ musicalization outside the project’s context. The chosen metodology was based on the qualitative approach with online semistructured interviews. The results indicate that this project had been a turning point on the kids’ development, due to their improvements on motor, cognitive, linguistic and musical abilities. I believe that this research can be an incentive for students’ involvement on future extension programs, oportunizing formation experiences and also contribute for the growth of our area.
Keywords: Música; Bebês; Crianças; Família; Musicalização; Music; Babies; Kids; Family; Musicalization; CNPQ::LINGUISTICA, LETRAS E ARTES